Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon - Lamboj, Anton (Zootaxa, 2005)
Nanochromis sabinae, a new cichlid species, is described from central and northeast Congo (Brazzaville) and southeast Gabon. It is differs from congeners in a combination of morphological characters and coloration patterns; e.g. anterior region of upper lateral line clearly separated from the dorsal-fin base; posterior nape scaled; one or two rows of cheek scales; a black longitudinal band from the eye to the end of the caudal peduncle, visible in both sexes in some behavioural situations but not extended into the caudal fin; females with some silvery colored scales around the genital papilla.